2020
DOI: 10.3390/ijerph17207644
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Weight Loss Results, Remission of Comorbidities and Nutritional Deficiencies of Sleeve Gastrectomy (SG), Roux-En-Y Gastric Bypass (RYGB) and One-Anastomosis Gastric Bypass (OAGB) on Type 2 Diabetic (T2D) Patients

Abstract: This study aimed to compare the long-term weight loss results, remission of comorbidities and nutritional deficiencies of sleeve gastrectomy (SG), Roux-en-Y gastric bypass (RYGB) and One-Anastomosis gastric bypass (OAGB) on type 2 diabetic (T2D) patients. Patients and Methods: A retrospective analysis of all the morbidly obese and diabetic patients undergoing SG, RYGB, and OAGB as primary bariatric procedures between February 2010 and June 2015 was performed. Anthropometric parameters, remission of comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 16 publications
(28 reference statements)
5
30
0
Order By: Relevance
“…Our findings extend and support some secondary and exploratory outcomes from the STAMPEDE trial, which showed that the proportion of patients with diabetes remission was non-significantly higher 1 year after gastric bypass than after sleeve gastrectomy (42% vs 27%), and that the proportion of patients not using any antidiabetic medication at 1 year was 78% after gastric bypass and 51% after sleeve gastrectomy (Castro et al, 2020).…”
Section: Resultssupporting
confidence: 86%
“…Our findings extend and support some secondary and exploratory outcomes from the STAMPEDE trial, which showed that the proportion of patients with diabetes remission was non-significantly higher 1 year after gastric bypass than after sleeve gastrectomy (42% vs 27%), and that the proportion of patients not using any antidiabetic medication at 1 year was 78% after gastric bypass and 51% after sleeve gastrectomy (Castro et al, 2020).…”
Section: Resultssupporting
confidence: 86%
“…This was also true for BMI reduction (p < 0.001) at one-year follow-up. Our results follow the findings in the literature [15]. According to Salvi et al [10], faster weight loss was reported in the first year after OAGB than after SG.…”
Section: Bmi-reduction and %Ewlsupporting
confidence: 92%
“…In all studies conducting a comparative analysis of the two procedures, RYGB was shown to have a higher %EWL at all periods, including two months, six months, and annually during years one to five postoperatively [16][17][18][19][20][21][22]. However, both the RYGB and SG show significant weight loss at all periods postoperatively.…”
Section: Weight Lossmentioning
confidence: 98%
“…Patients are asked to attend clinic follow-up visits for the continuance of weight loss measurement and post-operative assessments. Subsequent visits typically occur during the two-month to two-year postoperative period; however, some studies have followed patients for up to five years [16][17][18][19][20][21][22].…”
Section: Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation